Miocene Lonchocarpus (Papilionoideae) in San Esteban Tizatlán, Tlaxcala, Mexico. (March 2016) - Hernández-Damián, Ana Lilia; Calvillo-Canadell, Laura; Cevallos-Ferriz, Sergio R.S.; Sousa, Mario
Abstract: New leaflets from San Esteban Tizatlán, Tlaxcala, Mexico, are described and identified based on their leaf architecture. They have elliptic leaflets with pulvinate petiolule, entire margin, convex apex and base, well developed primary and craspedodromous secondary venation, with decurrent secondary veins with fused the mid-vein, a pair of obtuse basal veins, weak intersecundary veins, mixed percurrent tertiary venation dominated by the opposite type with sinuous course, alternate percurrent fourth-order venation, regular reticulate with few non ramified veinlets. All these characteristics are closely compared with members of sections Obtusifolii and Standleyi of Lonchocarpus (Leguminosae, Papillionoideae, Millettieae), but the mosaic of characters found in the fossil material granted recognition of a new species Lonchocarpus miocenicus sp. nov. This new record of Lonchocarpus from central Mexico further supports the presence of an evergreen tropical forest during the Miocene in the area, a plant community that developed from the Boreotropical Flora and contributed latter to the Neotropical Flora. Graphical abstract: Highlights: A new Miocene species of Lonchocarpus is described based on Leaf architecture. It supports the presence of an evergreen tropical forest during the Miocene in Central Mexico. Adds support to the idea of plants from North America became part of the extant Neotropical flora.